Natureza e organização dos lares residenciais para pessoas com deficiência em Portugal: relatório final = Nature and Organisation of Institutions for Persons with Disabilities in Portugal: final report - Lopes, Alexandra (2025)
Emphasis on the implications of Article 19 of the United Nations Convention on Rights of Persons with Disabilities (CRPD) - Persons with disabilities have the right to living independently and being included in the community - has led to a growing recognition that services provided in residential care facilities segregated from the community are somehow at odds with the Convention and with the principles and rights it defines. And although the CRPD does not make any explicit reference to closing institutions, it paves the way for deinstitutionalisation as the preferential route for the development of assistance and support services to persons with disabilities. This has translated into a growing visibility of the topic of deinstitutionalisation in the policy agenda of the European Union. The policy goals set in the Union for Equality - Strategy for the Rights of Persons with Disabilities 2021-2030 are clear in the vision of guaranteeing that persons with disabilities can effectively exercise theirright to live independently and be included in the community, with choices equal to those of others about their place of residence and with whom and how they live. In that same policy document, the European Commission (EC) states its commitment with supporting national, regional, and local authorities of Member States in their efforts for deinstitutionalisation and independent living.